2020
DOI: 10.1029/2020gc009227
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties of Ferritchromite and Cr‐Magnetite and Monitoring of Cr‐Spinels Alteration in Ultramafic and Mafic Rocks

Abstract: Rock magnetism methods can be judiciously used to recognize and understand some metamorphic processes. Serpentinization reactions, for example, generate a significant amount of magnetite that magnetic methods allow to efficiently identify and quantify (O'Hanley, 1996, p. 277). However, other magnetic phases

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
0
7
0
1
Order By: Relevance
“…The same holds true for Fe-Ti spinels and spinels with all three elements, though the magnetic properties of latter have not been thoroughly studied. We note that some of the Cr-magnetite grains in Hodel et al (2017) and Hodel et al (2020) are indeed ferromagnetic at room temperature and are therefore relevant.…”
Section: Relevant Terrestrial Iron Oxidesmentioning
confidence: 80%
See 1 more Smart Citation
“…The same holds true for Fe-Ti spinels and spinels with all three elements, though the magnetic properties of latter have not been thoroughly studied. We note that some of the Cr-magnetite grains in Hodel et al (2017) and Hodel et al (2020) are indeed ferromagnetic at room temperature and are therefore relevant.…”
Section: Relevant Terrestrial Iron Oxidesmentioning
confidence: 80%
“…Fe-Cr spinels can be ferromagnetic at room temperature depending on the amount of Cr substitution in the spinel structure (Hodel et al, 2020), and is discussed further in the next section.…”
Section: Relevant Terrestrial Iron Oxidesmentioning
confidence: 99%
“…In the literature on the zoned chromites described above, there is no mention of textures consistent with porous-chromite oxidation (Gervilla et al, 2019;Hodel et al, 2020). The volcanic rocks sampled by the studies cited above were observed to be fresh with little to no evidence of alteration, which is not consistent with a weathering environment capable of significantly modifying chromite compositions in either hydrothermal (Hodel et al, 2020) or metamorphic (Gervilla et al, 2019) regimes. Instead, since the chromite FeO and Al 2 O 3 concentrations are observed to increase from core to rim (which is a geochemical signature of magmatic oxidation in our model, i.e.…”
Section: Assessing Chromite-melt Equilibrium Based On Model Equilibrium Trivalent Cation Proportionsmentioning
confidence: 96%
“…The plot of the trivalent cations Al 3+ , Cr 3+ , and Fe 3+ differentiates among the Cr-Fe-spinels (Fig. 5b), and the criteria proposed by Barnes and Roeder (2001) and Hodel et al (2020) were adopted to define the compositional fields of magnetite sensu stricto (Cr 2 O 3 0-6 wt%), Cr-magnetite (Cr 2 O 3 6-13 wt%) and ferritchromite (Cr 2 O 3 > 13 wt%).…”
Section: Oxide Chemistry By Electron Microprobe (Epma)mentioning
confidence: 99%